Government Expenditure and Economic Growth in Euro Area Countries - Helena Cenc (Naše gospodarstvo/Our economy, 2022)
In this article, the author examines the impact of government expenditure on economic growth. A review of empirical studies shows that researchers have found a negative link between government spending and economic growth in most cases. This paper is based on yearly data between 1995 and 2020 in euro area countries, with the application of linear regression on panel data. The main purpose is to determine whether government spending affects economic growth and, if so, how. Based on the econometrics model applied, the author established that in panel data, government expenditure has a negative impact on economic growth, more precisely, if government spending as a share of GDP increases by 1%, economic growth decreases by 0.509%. In addition, there is a significant negative relationship between government expenditure and economic growth for each country as well as the entire panel.